Blockchain Integration in Academic Credentialing: Implications for Employment Markets and Economic Growth - Fahrezi, Muhamad (Universitas Komputer Indonesia, 2024)
The integration of blockchain technology in academic credentialing has the potential to revolutionize traditional systems of verifying educational achievements. The study aims to assess how blockchain can improve the efficiency, transparency, and security of academic qualification verification processes. Using a qualitative research approach, we analyzed current trends and reviewed of blockchain applications in education. The results indicate that blockchain technology significantly reduces credential fraud, enhances labor market mobility, and accelerates hiring processes. Furthermore, blockchain’s decentralized nature allows for greater control and ownership of academic credentials, making them more accessible and verifiable across borders. These findings highlight the transformative potential of blockchain to create a more efficient, equitable, and globalized labor market. As a result, blockchain could not only streamline employment practices but also drive economic growth by improving human capital utilization and fostering global talent mobility